2006
DOI: 10.1086/504846
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Outflows in Galaxy Merger Simulations with Embedded Active Galactic Nuclei

Abstract: We study the effects of feedback from active galactic nuclei (AGNs) on emission from molecular gas in galaxy mergers by combining hydrodynamic simulations that include black holes with a three-dimensional, non-local thermodynamic equilibrium (LTE) radiative transfer code. We find that molecular clouds entrained in AGN winds produce an extended CO morphology with significant off-nuclear emission, which may be detectable via contour mapping. Furthermore, kinematic signatures of these molecular outflows are visib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 51 publications
(71 reference statements)
10
78
1
Order By: Relevance
“…This suggests a solution to the long-standing problem of the transport of energy from the nucleus to the bulk of the galaxy: a highly supersonic shock transports outwards the energy accumulated in the center by radiatively accelerated nuclear winds. Extended emission and kinematic signatures in the CO line profiles similar to those observed here are predicted by hydrodynamic simulations that study the effect of AGN feedback on the molecular gas (Narayanan et al 2006(Narayanan et al , 2008. Owing to the simultaneous presence of a strong wind, heavy X-ray absorption, and of high star-formation rate, Mrk 231 has been regarded as one of the promising candidates of a QSO transiting from the obscured accretion phase, accompanied by vigorous star formation, where AGN feedback onto the host galaxy is in action, to the un-obscured phase (Page et al 2004;Stevens et al 2005) in the framework of the AGN-galaxy co-evolutionary sequence.…”
Section: Discussionsupporting
confidence: 77%
“…This suggests a solution to the long-standing problem of the transport of energy from the nucleus to the bulk of the galaxy: a highly supersonic shock transports outwards the energy accumulated in the center by radiatively accelerated nuclear winds. Extended emission and kinematic signatures in the CO line profiles similar to those observed here are predicted by hydrodynamic simulations that study the effect of AGN feedback on the molecular gas (Narayanan et al 2006(Narayanan et al , 2008. Owing to the simultaneous presence of a strong wind, heavy X-ray absorption, and of high star-formation rate, Mrk 231 has been regarded as one of the promising candidates of a QSO transiting from the obscured accretion phase, accompanied by vigorous star formation, where AGN feedback onto the host galaxy is in action, to the un-obscured phase (Page et al 2004;Stevens et al 2005) in the framework of the AGN-galaxy co-evolutionary sequence.…”
Section: Discussionsupporting
confidence: 77%
“…The stellar masses ranged from ∼ 3 − 8 × 10 11 M , and the galaxies lived in haloes ranging from ∼ 7 − 20 × 10 12 M . (Narayanan et al, 2006a(Narayanan et al, ,b, 2008b) 3D non-LTE Monte Carlo molecular line radiative transfer calculations in post-processing. These authors found that SMGs that formed in galaxy mergers show broad CO line widths, varied CO morphologies, and typically subthermal CO excitation, comparable to previous observations (c.f.…”
Section: Idealized and Hybrid Simulationsmentioning
confidence: 99%
“…Double-horned profiles, as in SW022550, are often found in merging galaxies, for example submillimeter galaxies (e.g., Frayer et al 1998;Neri et al 2003;Tacconi et al 2006;Bothwell et al 2010), and may either signalize a rotating disk or a merger of two reservoirs of molecular gas (e.g., Neri et al 2003;Taniguchi & Shioya 1998;Sakamoto et al 1999;Narayanan et al 2006;Downes & Solomon 1998;Evans et al 1999). However, double-peaked profiles with FWHM ≥ 300 km s −1 per peak are rarely observed.…”
Section: Are the Line Profiles In Our Sources Typical?mentioning
confidence: 99%